Kajian Material dan Kajian Formal Dakwah - Afandi, Masduqi (Proceedings of International Conference on Da'wa and Communication, 2019)
This paper consists of two studies that we make one, the first is titled scientific da’wa and the second is the nature of da’wa. The first research focuses on the discovery of the study of da’wa material and the second describes the formal study of da’wa through its properties, with the first research being philosophical in nature while the second is empirical by observing three sermon events. The method in this study uses heuristics because they really want to find a new field of science. The question asked is what is the material study and formal study of da’wa, the conclusion shows that the material study is the substance of da’wa while the material study is the properties inherent in the substance of da’wa.